Analisis Sosiologis Novel dan Aplikasinya dalam Pembelajaran Unsur Ekstrinsik Karya Sastra di SMP - Puji Anto (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2016)
The purpose of this study was to analyze the sociological elements of the novel and its application in the teaching of Indonesian language and literature. The method used to analyze the novel is by using descriptive method. After the authors analyzed the novel Ranah 3 Warna through elemental analysis of sociological, finally the author can draw the conclusion that the element of sociological contained in the novel Ranah 3 Warna focus of study on the theme